Matthew - Talbert, Charles H. (Paideia - commentaries on the New Testament, 2010)
A leading New Testament scholar examines cultural context and theological meaning in Matthew. This commentary approaches each text in its final, canonical form, proceeding by sense units rather than word-by-word or verse-by-verse. Each sense unit is explored in three sections: (1) introductory matters, (2) tracing the train of thought, (3) key hermeneutical and theological questions--From publisher description